WHAT KIND OF HEALTH CARE SYSTEM WILL SELECT THE UKRAINE? - Vazkes Abanto, H. (World of Medicine and Biology, 2013)
Powerful system of Semashko undoubtedly long since become irrelevant for the countries of the former Soviet Union in the present socio-economic conditions. Free medical care for the whole population, "young and old", guaranteed by the state, did work, even though we know that health care is often underfunded. Times have changed and the health care system Semashko, like others in the world, have largely become irrelevant. Discuss and debate on the subject of the quality and other components of a system is not our purpose today. The purpose of this article - to learn pre-existing health systems today and in the world, and to evaluate the current process of health care reform, where the leading role WHO's efforts have, therefore in the work highlights the key, in our view, highlights the organization's activities in this area.
Keywords: medicine; health care; public health; WHO; health care reform